Combined Treatment with Low Cytotoxic Ethyl Acetate Nepenthes Extract and Ultraviolet-C Improves Antiproliferation to Oral Cancer Cells via Oxidative Stress - Sheng-Yao Peng; Li-Ching Lin; Zhe-Wei Yang; Fang-Rong Chang; Yuan-Bin Cheng; Jen-Yang Tang; Hsueh-Wei Chang (MDPI AG, 2020)
Ultraviolet-C (UVC) irradiation provides an alternative radiotherapy to X-ray. UVC sensitizer from natural products may improve radiotherapy at low cytotoxic side effects. The aim of this study is to assess the regulation for oral cancer cell proliferation by a combined treatment of UVC and our previously reported anti-oral cancer natural product (ethyl acetate extract of Nepenthes adrianii × clipeata; EANA). The detailed possible UVC sensitizing mechanisms of EANA such as effects on cell proliferation, cell cycle, apoptosis, and DNA damage are investigated individually and in combination using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTS) assay, flow cytometry, and western blotting at low dose conditions. In a 24 h MTS assay, the low dose EANA (5 μg/mL) and low dose UVC (12 J/m2) individually show 80% and combinedly 57% cell proliferation in oral cancer Ca9-22 cells; but no cytotoxicity to normal oral HGF-1 cells. Mechanistically, low dose EANA and low dose UVC individually induce apoptosis (subG1 accumulation, pancaspase activation, and caspases 3, 8, 9), oxidative stress (reactive oxygen species, mitochondrial superoxide, and mitochondrial membrane potential depletion), and DNA damage (γH2AX and 8-hydroxy-2'-deoxyguanosine). Moreover, the combined treatment (UVC/EANA) synergistically induces these changes. Combined low dose treatment-induced antiproliferation, apoptosis, oxidative stress, and DNA damage were suppressed by the ROS scavenger N-acetylcysteine. In conclusion, UVC/EANA shows synergistic antiproliferation, oxidative stress, apoptosis, and DNA damage to oral cancer cells in an oxidative stress-dependent manner. With the selective killing properties of low dose EANA and low dose UVC, EANA provides a novel UVC sensitizing agent to improve the anti-oral cancer therapy.